First report of a carbapenemase gene blaOXA-181 harbored in a conjugative plasmid in Kluyvera sichuanensis isolated from spinach - Xu Yang; Jinkyung Kim; Nhu-Y Do; Xinhui Li; En Huang; Se-Ran Jun; Sun Hee Moon; Erin L. DiCaprio; Shuting Chen (International Journal of Food Microbiology, 2026)

Comprehensive analyses of carbapenem-resistant and ESBL-producing bacteria in fresh vegetables and their resistome in the United States - Sun Hee Moon; Xu Yang; Jinkyung Kim; Elizabeth Leighton; Se-Ran Jun; Erin DiCaprio; Chelsea Gale; Shuting Chen; Xinhui Li; En Huang (Food Research International, 2026)

Mixed exposure to brominated flame retardants adversely affects vaccine-induced antibody titers: Risk prioritization and benchmark dose modeling - Zihui Zhao; Chi Zhang; Xueyu Chen; Yongheng Yan; He Jiao; Xianhao Wang; Ruxu Yan; Yiqian Wang; Meng Liu; Xianfeng Yue; Yuqian Sui; Xia Li; et al. (Toxicology Letters, 2026)

Calcium signaling and hormonal regulation mediate Trichoderma harzianum NDT-1-induced resistance against postharvest gray mold in tomato - Yawen Wang; Zhenshuo Wang; Ruoyu Wu; Shuting Chen; Baojuan Sun; Weijie Xu; Tao Li; Yuyang Zhang; Yanwei Hao; Chao Gong (Postharvest Biology and Technology, 2026)

Rethinking Ship Emission Hotspots: A 100 m Resolution AIS-Based Inventory for Coastal Chinese Waters - Shuting Sun; Huihui Zhao; Xianchao Yang; Li Zhu; Wei Han (Journal of Marine Science and Engineering, 2026)
Existing ship emission inventories for coastal seas are typically gridded at 500 m to 1 km, a resolution too coarse to distinguish navigation channels from anchorage zones. Whether the hotspot patterns reported at such scales reflect true emission geography or are artifacts of spatial averaging remains an open question. We construct a 100 m resolution AIS-based emission inventory for two contrasting coastal environments in eastern China—the Yangtze River estuary and the Wenzhou coastal area—using the STEAM framework, and we quantify spatial concentration with Lorenz curve analyses. At this finer resolution, three emission archetypes become separable: discrete anchorage clusters, bankside berthing bands flanking navigation lanes, and sinuous riverbank traces in confined waterways. Emissions are extremely concentrated: the top 1% of grid cells capture over three-quarters of the total theoretical emission potential (Gini = 0.940), and this pattern persists across all months of 2023. Reaggregating the same data to 1 km reduces the top-1% share by roughly 10%, confirming that coarse gridding systematically understates anchorage contributions while overstating those of transit corridors. A dedicated sensitivity analysis on auxiliary engine load assumptions (±30% perturbation of canonical Jalkanen-style load brackets) shows that, while absolute emission totals carry approximately ±15% uncertainty, the spatial concentration of emissions is highly robust: Across all perturbation scenarios, the Gini coefficient varies by less than 0.01, the top-5% emission share varies by less than 2 percentage points, and the location of top-5% hotspot cells overlaps by ≥97.9% (Jaccard index). The results highlight stationary vessel hotspots—discrete anchorages and bankside berths—as a major and previously underemphasized contributor to the cumulative coastal ship emission budget, complementing rather than replacing the conventional navigation-lane focus, with direct implications for shore power siting, anchorage management, and emission control zone design.

Study on the improvement effect and mechanism of resveratrol on cognitive impairment in tau mutant adenovirus-induced alzheimer’s disease model mice - Shuting Chen; Kexuan Zhao; Zhidan Shi; Chu Zhang; Hao Wu; Meng Tian; Yi Sun; Ling He (Psychopharmacology, 2026)

Research on flexural performance of bolt-spliced joints in precast H-shaped steel support structure - Yinjie Lu; Shuting Liang; Xiaojun Zhu; Dongyue Wu; Wenkang Wang; Yuanyuan Sun; Bowei Sun (Engineering Structures, 2026)

Anammox dominated As(V/III) speciation during long-term anaerobic conditions - Taicong Liu; Shuting Tang; Yingpeng Sun; Zhongtao Lao; Daijie Chen; Ming Ao; Haojie Qu; Chao Jin; Liying Lan; Roland Bol; Miaoyue Zhang; Yingjie Cao; et al. (Soil Biology and Biochemistry, 2026)

Multi-objective optimization study of wire mesh mist eliminator based on RSM and NSGA-II - Shuting Zhong; Shaochen Yang; Rulei Sun; Ruifeng Tian; Sichao Tan; Chaojun Deng; Bo Wang (Annals of Nuclear Energy, 2026)

Correlation analysis of monosaccharide composition and in vitro antioxidant and hypoglycemic activities of Tremella fuciformis spore polysaccharides - Jianqiu Chen; Xiaoyu He; Shuting Zhou; Yujie Chen; Chunyuan Kong; Yating Deng; Shikai Ruan; Chengzhen Gu; Shujing Sun (Food Chemistry, 2026)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Shaking table test of a frame structure with phononic-like crystal polymer concrete seismic mitigation raft foundation - Shuting Liang; Yuanyuan Sun; Xiaojun Zhu; Linchang Miao; Zhongzhen Xie; Jian Yang (Soil Dynamics and Earthquake Engineering, 2025)

Natural, tough and pH-responsive ultrasound modified soy protein isolate-arabinoxylan based double network hydrogels for controlled nutrients release - Ran Tao; Gaolin Li; Siyang Wang; Yufeng Sun; Yurui Li; Peiying Wang; Shuting Huang; Bei Fan; Fengzhong Wang (Food Hydrocolloids, 2025)

Antioxidant and antimicrobial sodium alginate/sodium carboxymethyl cellulose films loaded with self-assembled hesperidin nanorods for fruits preservation - Zexin Gao; Shuting Xie; Li Chang; Huijuan Tang; Zhimin Sun; Yong Deng; Yinqi Hu; Ying Xu; Mingbao Luan (Food Chemistry, 2025)

Adsorptive removal of radioactive technetium by nanomaterials - Jingyang Sun; Xiaolian Yi; Chang Yuan; Wangming Zhu; Mingjia Liao; Yiyang Ye; Dameng Liu; Huan Liu; Shuting Zhuang (Reviews in Environmental Science and Bio/Technology, 2025)

Multi-objective optimization design of double-hooked corrugated plate dryer based on NSGA-II - Zhong Shuting; Sun Rulei; Li Yang; Qin Qi; Deng Chaojun; Wang Bo; Tian Ruifeng (Annals of Nuclear Energy, 2025)

Spatial-Temporal Ship Pollution Distribution Exploitation and Harbor Environmental Impact Analysis via Large-Scale AIS Data - Xinqiang Chen; Shuting Dou; Tianqi Song; Huafeng Wu; Yang Sun; Jiangfeng Xian (Journal of Marine Science and Engineering, 2024)
Ship pollution emissions have attracted increasing attention in the maritime field due to the massive growth of maritime traffic activities. It is important to identify the ship emissions (SEs) magnitude and corresponding spatial and temporal distributions for the purposes of developing appropriate strategies to mitigate environment pollution. The aim of this study was to estimate ship pollution emissions with various typical merchant ship types under different sailing conditions. We estimated the emission variation with a ship traffic emission assessment model (STEAM2), and then the ship pollution emission distribution was further visualized using ArcGIS. We collected data from the automatic identification system (AIS) for ships in New York Harbor and further analyzed the spatiotemporal distribution of pollutant emissions from ships. The experimental results demonstrate that the ship pollutant emission volume in the New York Harbor area in 2022 was 3340 t, while the pollution in terms of CO, SO2, CXHX, PM10, NOX, and PM2.5 was 136, 1421, 66, 185, 1384, and 148 t, respectively. The overall SEs from container ships, passenger ships, and tankers account for a large amount of pollution discharge. The pollutant emissions of container ships are significantly greater than that of their counterparts. Moreover, the spatiotemporal distributions of ship pollutant discharge can vary significantly among different ship types and sailing conditions.

Ruthenium decorated nickel-iron layered double hydroxides (NiFe-LDH) for promoting peroxymonosulfate activation and atrazine degradation - Yu Yin; Shuting Pan; Jiajie Lu; Abdul Hannan Asif; Sheng Cui; Shaobin Wang; Hongqi Sun (Journal of Environmental Chemical Engineering, 2024)

The effects of different drying methods on the flavor profile of wheat germ using E-nose and GC-IMS - Yang Zhong; Gexing Zhang; Fangqin Zhang; Shuting Lin; Mei Wang; Yue Sun; Jin Liang; Xueling Li (Journal of Cereal Science, 2024)

Analysis of actual evapotranspiration changes in China based on multi-source data and assessment of the contribution of driving factors using an extended Budyko framework - Tao Su; Shuting Wang; Siyuan Sun; Taichen Feng; Bicheng Huang; Qianrong Ma; Shuping Li; Guolin Feng (Theoretical and Applied Climatology, 2024)

A facile method to construct ZIF-8 MOFs on contact lens for high antibiotics loading and self-defensive release - Yi Shao; Hao Suo; Shuting Wang; Yaou Peng; Xiaoying Chu; Ziyue Long; Kanghui Du; Lili Su; Xinyue Sun; Xinyi Wang; Qingying Wang; Renlong Li; et al. (Chemical Engineering Journal, 2024)

Bioleaching rare earth elements from coal fly ash by Aspergillus niger - Juanjuan Ma; Shuyan Li; Jinxi Wang; Shuting Jiang; Balaji Panchal; Yuzhuang Sun (Fuel, 2023)

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

Characterization, expression, and function analysis of AKR1A1 gene from yellow catfish (Tachysurus fulvidraco) - Long Yang; Shuting Zheng; Dan Kong; Shenghan Xiang; Jianfen Wu; Neng Wan; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Arsenic exposure increased expression of HOTAIR and LincRNA-p21 in vivo and vitro - Jingwen Tan; Mingjun Sun; Quan Luo; Huiwen Sun; Mengjie Wang; Chenglan Jiang; Shuting Li; Yuefeng He (Environmental Science and Pollution Research, 2021)

G604S-HERG mutation in LQT2 leads to autophagy via the UPR-related pathway - Yun Zhao; Shuting Ma; Miaomiao Cao; Chaofeng Sun (Journal of Biosciences, 2020)

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

EEG-based mild depression recognition using convolutional neural network - Xiaowei Li; Rong La; Ying Wang; Junhong Niu; Shuai Zeng; Shuting Sun; Jing Zhu (Medical & Biological Engineering & Computing, 2019)

Study and Application of the Interaction Between Asymmetrical Porphyrin and Ascorbic Acid - Shuting Sun; Dan Wu; Qin Wei; Yanyan Han; Xin Chen; Yunxia Shen; Peihua Zhu; Bin Du (Journal of Fluorescence, 2009)